2007
DOI: 10.1007/s10854-007-9306-5
|View full text |Cite
|
Sign up to set email alerts
|

In-situ optical reflectance and synchrotron X-ray topography study of defects in epitaxial dilute GaAsN on GaAs

Abstract: In order to investigate the possibilities of in-situ monitoring of GaAsN bulk layer growth and the crystal quality concerning the formation of misfit dislocations, GaAsN bulk samples with different layer thicknesses were grown using a metal-organic vapor phase epitaxy system equipped with a normal incidence optical reflectance setup. High-resolution X-ray diffractometry and synchrotron radiation X-ray topography were used to characterize the samples after growth. Combining the results from topography images an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The cross-hatch surface morphology is usually recognized to be directly related with strain relaxation via threading dislocation glide which results in both surface step and misfit dislocation formation [9,10]. Such a morphology is often observed during strain relaxation in many III-V lattice mismatched semiconductor systems, such as GaInAs/GaAs [11,12] or GaNAs/GaAs [13,14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-hatch surface morphology is usually recognized to be directly related with strain relaxation via threading dislocation glide which results in both surface step and misfit dislocation formation [9,10]. Such a morphology is often observed during strain relaxation in many III-V lattice mismatched semiconductor systems, such as GaInAs/GaAs [11,12] or GaNAs/GaAs [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…dislocation nucleation and glide. As a consequence, the asymmetric 2D network of  and  dislocations, running in two perpendicular 110 directions is usually formed, resulting in anisotropic misfit strain relaxation of the epitaxial layer in these directions [11][12][13][14][15][16][17]. Indeed, our previous studies on the GaInNAs/GaAs heterostructure showed a distinct anisotropy of strain relaxation related to the asymmetry in formation of interfacial dislocation network [8].…”
Section: Resultsmentioning
confidence: 99%
“…The resultant undulating surface morphology, known as a cross-hatch pattern, is formed. The crosshatch morphology is often observed after strain relaxation of many (001)-oriented cubic semiconductor systems, such as GeSi/Si [12], GaInAs/GaAs [13,14], or GaNAs/GaAs [15] and it is usually recognized to reproduce a network of underlying interfacial misfit dislocations. A detail analysis of the GaInNAs surface morphology, related to formation of a misfit dislocations network, will be the subject of our forthcoming investigations.…”
Section: Resultsmentioning
confidence: 99%